URGENSI PENDIDIKAN SEKS PADA SISWA MADRASAH IBTIDAIYAH DALAM UPAYA PENCEGAHAN PERILAKU PENYIMPANGAN SEKSUAL DI KABUPATEN JOMBANG - Achmad Anwar Abidin; Muammar Luthfi (Jurnal Ilmiah Didaktika, 2016)
Experts say sexual deviation is caused by several factors including hormone disorder, genetic potential, environmental factors and also improper sex education. Education also contributes to the occurrence of sexual perversion. Therefore, proper sex education at an early age is necessary to prevent sexual deviant behavior. Sexual deviance behavior is a disease that can be known if the patient is already Mumayiz or legally baligh for the needs of one's sex began to be felt. due to there are many people suffered from sexual deviance behavior, then we should be able to detect and prevent them early.